Musculoskeletal pain in Europe: the role of personal, occupational, and social risk factors - Farioli, Andrea; Mattioli, Stefano; Quaglieri, Anna; Curti, Stefania; Violante, Francesco S; Coggon, David (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'The prevalence of musculoskeletal pain in European countries varies considerably. We analyzed data from the fifth European Working Conditions Survey (EWCS) to explore the role of personal, occupational, and social risk factors in determining the national prevalence of musculoskeletal pain. ' ' METHODS ': 'Over the course of 2010, 43 816 subjects from 34 countries were interviewed. We analyzed the one-year prevalence of back and neck/upper-limb pain. Individual-level risk factors studied included: sex; age; educational level; socioeconomic status; housework or cooking; gardening and repairs; somatizing tendency; job demand–control; six physical occupational exposures; and occupational group. Data on national socioeconomic variables were obtained from Eurostat and were available for 28 countries. We fitted Poisson regression models with random intercept by country. ' ' RESULTS ': 'The main analysis comprised 35 550 workers. Among individual-level risk factors, somatizing tendency was the strongest predictor of the symptoms. Major differences were observed by country with back pain more than twice as common in Portugal (63.8%) than Ireland (25.7%), and prevalence rates of neck/upper-limb pain ranging from 26.6% in Ireland to 67.7% in Finland. Adjustment for individual-level risk factors slightly reduced the large variation in prevalence between countries. For back pain, the rates were more homogenous after adjustment for national socioeconomic variables. ' ' CONCLUSIONS ': 'Our analysis indicates substantial variation between European countries in the prevalence of back and neck/upper-limb pain. This variation is unexplained by established individual risk factors. It may be attributable in part to socioeconomic differences between countries, with higher prevalence where there is less risk of poverty or social exclusion.
Keywords: back pain; cross-sectional study; Europe; European Working Conditions Survey; EWCS; musculoskeletal disease; musculoskeletal pain; neck pain; occupational risk factor; personal risk factor; population characteristic; social risk factor; upper-limb pain